An Investigation into Saudi Arabian Final-year Student Teachers’ Competency to Teach English as a Foreign Language - Elshamy, Ahmed; Sheik, Ayub (International Journal of English Language Education, 2022)
This study aimed to investigate final-year English major Saudi student teachers’ competency to teach English as a foreign language (EFL) in schools after they graduate. There were two research objectives: identifying final-year student teachers’ actual preparedness to teach EFL; exploring their perceptions of preparedness to teach EFL after graduation. An interpretive approach was employed to explore their actual preparedness to teach English as evidenced in established metrics such as Cambridge Teaching Knowledge Test (TKT) in relation to their perceptions of competency. This qualitative process was complimented by focus group discussions to explore student perceptions of their ability to teach EFL upon graduation. A total of 26 final-year student teachers were chosen to represent the sample of this study. All student teachers completed the TKT, from which six candidates were selected for the focus group discussions. The results of the TKT revealed that most of the student teachers fall into Band 2 (as per the established Band Descriptors of the TKT), which means that their teaching knowledge is satisfactory. The focus group discussions further indicated that most participants felt that the B.A. programme only partially prepared them to teach English upon graduation. Student teachers’ views varied regarding their competency to teach the four language skills with most student teachers perceiving themselves as not prepared to start EFL teaching upon graduation. The broader implications of these findings suggest that a curriculum review and pedagogical best practice needs to be implemented in the BA programme at the university which is intended to produce competent EFL teachers.